Ab Initio and DFT Studies of Conformational Properties of Heteroatom Containing Ketene Analogues and Their Comparison with the Related Cyclic Analogues - S. Zahra Sayyed-Alangi; Mohammad T. Baei (E-Journal of Chemistry)
Minimum-energy and transition state geometries of 3-thioxoprop-2-enethial, 3-thioxoacrylaldehyde, 3-oxoprop-2-enethial, 3-selenoxoprop-2-enethial, 3-thioxoprop-2-eneselenal, 3-selenoxoprop-2-eneselenal, 3-oxoacrylaldehyde, 3-selenoxoacrylaldehyde and 3-oxoprop-2-eneselenal were calculated using HF, B3LYP and MP2 levels of theory and 6-31+G* basis set by rotation around the related -C-C- single bonds. In all of the above mentioned molecules, the s-trans conformation was obtained as the most stable conformer with the 180° dihedral angle, apart from 3-oxoprop-2-enethial and 3-thioxoprop-2-eneselenal which their s-cis conformers were appeared more stability than related to s-trans forms. Their perpendicular geometries, with torsional angles approximately 90°, were as transition state for conformational interconversion between the two global minima forms. Cyclic structures all of the above mentioned molecules were unstable than their linear forms.